1998
DOI: 10.1007/s001010050600
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrische Notfälle aus der Sicht von Notärzten

Abstract: PES are a frequent problem of pre-hospital patient care for emergency physicians. As personal knowledge was estimated to be insufficient, the interest for courses concerning PES issues is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…In contrast to the internalized uncertainty of the inexperienced PSs, experienced PHEPs most frequently stated that they felt insufficiently qualified to handle psychiatric emergencies. Pajonk et al already identified a possible deficit in the qualification of German PHEPs for the treatment of psychiatric emergency patients some 20 years ago [ 18 ]. To improve their skills in the treatment of psychiatric emergencies, PHEPs stated in a survey that they were willing to complete a one-day internship in a psychiatric hospital [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the internalized uncertainty of the inexperienced PSs, experienced PHEPs most frequently stated that they felt insufficiently qualified to handle psychiatric emergencies. Pajonk et al already identified a possible deficit in the qualification of German PHEPs for the treatment of psychiatric emergency patients some 20 years ago [ 18 ]. To improve their skills in the treatment of psychiatric emergencies, PHEPs stated in a survey that they were willing to complete a one-day internship in a psychiatric hospital [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for obtaining the additional qualification in emergency medicine do not differ in principle between university hospitals and smaller hospitals due to centrally organized training courses and exams. Therefore, according to the current evidence, it can be assumed that the qualification deficit of PHEPs in the treatment of psychiatric patients, which has already been addressed, exists independently of their experience [ 6 , 7 , 18 ]. The level of training of the psychiatrists surveyed in the participating psychiatric hospitals is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Die Qualifikation von Rettungsassistenten und Notärzten unterliegt nach wie vor sehr starken Schwankungen [12]. Während der Nachholbedarf für psychiatrische Notfälle zumindest bereits erkannt ist [10,19], sind psychische Ausnahmezustände bisher wenig von Notärzten thematisiert worden. Während der Nachholbedarf für psychiatrische Notfälle zumindest bereits erkannt ist [10,19], sind psychische Ausnahmezustände bisher wenig von Notärzten thematisiert worden.…”
Section: Basiskrisenintervention -Notarzt Oder Rettungsassistent?unclassified
“…Psychiatrische Notfälle stellen für die im Rettungsdienst Tätigen selbst eine schwere psychische Belastung dar [3,4]. Das eigene Risiko für eine posttraumatische Belastungsstörung oder eine Depression beträgt rund 10 %, wobei eine vorbestehende psychiatrische Störung das Risiko um das 5-bis 6-Fache erhöht [5].…”
Section: Introductionunclassified